Witch & wizard Volume 3 - Patterson, James, 1947- (Patterson, James, 1947- Witch & wizard novels., 2013)
"Although Whit and Wisty's magic and their control over it have matured, they still find themselves helpless to prevent the one who is the one from destroying everyone and everything they hold dear. But there's a reckoning on the horizon, and the siblings have no choice but to devise a strategy to topple with one decisive blow the tyrant who has devastated their world before he becomes truly all-powerful" -- p. [4] of cover.